Moral Goals and Legal Coercion: Philosophical and Legal Arguments of Patrick Devlin - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the arguments of the British jurist P. Devlin on the possibility of ensuring the achievement of moral goals by legal means. The views of P. Devlin and his debate with H. L. A. Hart gave rise to deep discussions on the relationship between moral and legal prescriptions in legislation and the search for moral grounds for legal norms and practice of its application. The paper also reconstructs P. Devlin’s arguments on the specifics of the application of the principle of harm compensation in assessing actions that contradict public morality